2023
DOI: 10.1021/acs.biochem.3c00338
|View full text |Cite
|
Sign up to set email alerts
|

HDX-MS Reveals Substrate-Dependent, Localized EX1 Conformational Dynamics in the Retaining GT-B Glycosyltransferase, MshA

Ramesh Karki,
Jacquelyn T. Hennek,
Wen Chen
et al.

Abstract: Glycosyltransferases (GTs) are well-characterized with respect to static 3D structures and molecular dynamics simulations, but there is a lack of reports on in-solution dynamics on time scales relevant to turnover. Here, backbone amide hydrogen/deuterium exchange followed by mass spectrometry (HDX-MS) was used to investigate the in-solution dynamics of the model retaining GT MshA from Corynebacterium glutamicum (CgMshA). CgMshA has a GT-B fold and catalyzes the transfer of N-acetyl-glucosamine (GlcNAc) from UD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The N-acetyl sugar offers no stabilization of either enzyme (data not shown) emphasizing the affinity afforded by the UDP moiety. The results are consistent with known specificity of C. consisus PglA enzymes for UDP-GalNAc and with previous observations that the resulting UDP binds and stabilizes the GT-B fold (Karki et al, 2023).…”
Section: Donor Substrate Specificity Of Pglasupporting
confidence: 92%
“…The N-acetyl sugar offers no stabilization of either enzyme (data not shown) emphasizing the affinity afforded by the UDP moiety. The results are consistent with known specificity of C. consisus PglA enzymes for UDP-GalNAc and with previous observations that the resulting UDP binds and stabilizes the GT-B fold (Karki et al, 2023).…”
Section: Donor Substrate Specificity Of Pglasupporting
confidence: 92%
“…The UDP product and UDP-GlcNAc substrate MshA complexes behave more similarly to one another with similar denaturation curves and decreases in intrinsic fluorescence. These results are in line with recent HDX-MS data showing that binding UDP or UDP-GlcNAc affects deuterium incorporation into similar regions of MshA …”
Section: Discussionmentioning
confidence: 99%
“…This view obscures a role for changes in localized protein dynamics in response to ligand binding and in shifting equilibrium from the open to closed state. For example, a recent HDX-MS study on MshA identified several regions that exhibit changes in deuterium uptake upon formation of liganded MshA complexes at areas distal to the site of ligand binding . In this study, we aim to utilize molecular dynamics (MD) and replica exchange molecular dynamics (REMD) simulations to identify the regions of MshA that undergo changes in fluctuations with respect to open/closed conformations and ligand binding over the 2 μs simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The glycosylation reaction in these GTs can proceed with either inversion or retention of stereochemistry at the C1 position of the nucleotide sugar. Some of these GTs combine both polymerizations of nucleotide sugars in an S N 2-like nucleophilic displacement reaction and translocate the growing polymer across the plasma membrane through its own transmembrane pore 6, 7 . The glycan polymers synthesized by these GTs contain tens of thousands of monomeric sugar units and can be extremely long 4, 8 .…”
Section: Introductionmentioning
confidence: 99%